Powerful professional development : building expertise within the four walls of your school - Yendol-Hoppey, Diane; Dana, Nancy Fichtman (Washington, D.C. : Distributed by ERIC Clearinghouse, 2000)
Two bodies of literature define the process for developing electronic teaching portfolios to support long-term professional growth: the multimedia development process (decide/assess, design/plan, develop, implement, evaluate) and the portfolio development process (collection, selection, reflection, projection/direction, presentation). As further defined, the Electronic Portfolio Development Process covers the following stages: (1) defining the portfolio context and goals; (2) the working portfolio; (3) the reflective portfolio; (4) the connected portfolio; (5) and the presentation portfolio. In addition, there are at least five levels of technology for developing electronic portfolios based on ease of use, including technologies that are appropriate at each level and stage. This combined process creates a foundation for powerful professional development. (Author/MES)
Microfiche.
Keywords: Computer Uses in Education; Educational Technology; Faculty Development; Material Development; Multimedia Materials; Portfolios (Background Materials); Teacher Education; Electronic Portfolios; Reports, Descriptive; Speeches/Meeting Papers